TEACHERS’ QUESTIONS IN INDONESIAN EFL CLASSROOM - Ahmadi; Kurniawan, Eri (JL3T (Journal of Linguistics, Literature and Language Teaching), 2020)
Despite the abundant advantages of teacher's questions, teachers still do not gain any benefits from them as they face many challenges in posing them. However, teachers who pose questions as a part of the teaching-learning strategy in the class may gain different outputs. A descriptive qualitative study is carried out to find out the types of questions that dominantly posed by a teacher in the intensive listening course at an institute of Islamic studies in Ponorogo. A lecturer and her class took part as participants on the study. Class observations, videotape observation, and interviews were utilized to gather the data. The revised Bloom’s taxonomy process verbs, assessment and questioning strategies was employed to analyze the data. The finding shows that the lecturer spent 73.8 percent of her questions on remembering, 17.8 percent on the understanding level, 5.9 percent on analyzing, and 2.9 percent on the evaluating level. It indicates that her questions were dominated by a low level of thinking skill.